Micromechanical Behavior of DNA-1A Lunar Regolith Simulant in Comparison to Ottawa Sand - Sandeep, C. S.; Marzulli, Valentina; Cafaro, F.; Senetakis, K.; Pöschel, Thorsten (Journal of Geophysical Research. Solid Earth, 2019)
In this study, the micromechanical interparticle contact behavior of “De NoArtri” (DNA-1A) grains is investigated, which is a lunar regolith simulant, using a custom-built micromechanical loading apparatus, and the results on the DNA-1A are compared with Ottawa sand which is a standard quartz soil. Material characterization is performed through several techniques. Based on microhardness intender and surface profiler analyses, it was found that the DNA-1A grains had lower values of hardness and higher values of surface roughness compared to Ottawa sand grains. In normal contact micromechanical tests, the results showed that the DNA-1A had softer behavior compared with Ottawa sand grains and that cumulative plastic displacements were observed for the DNA-1A simulant during cyclic compression, whereas for Ottawa sand grains elastic displacements were dominant in the cyclic sequences. In tangential contact micromechanical tests, it was shown that the interparticle friction values of DNA-1A were much greater than that of Ottawa sand grains, which was attributed to the softer contact response and greater roughness of the DNA-1A grains. Widely used theoretical models both in normal and tangential directions were fitted to the experimental data to obtain representative parameters, which can be useful as input in numerical analyses which use the discrete element method.
CRIS-Team Scopus Importer:2019-08-27
Keywords: interparticle friction; lunar regolith simulant; micromechanics; quartz sand